Diazepam-induced transcriptional regulation of GABAA receptor alpha 1 subunit via L-type voltage-gated calcium channel activation1 subunit gene in rat cerebrocortical neurons - Medina, Nelsy Beatriz (2019)
GABA-A receptors are targets of different pharmacologically relevant drugs, such as barbiturates, benzodiazepines, and anesthetics. In particular, benzodiazepines are prescribed for the treatment of anxiety, sleep disorders, and seizure disorders. Prolonged activation of GABA-A receptors by endogenous and exogenous modulators induces adaptive changes that lead to tolerance. For example, chronic administration of benzodiazepines produces tolerance to most of their pharmacological actions, limiting their usefulness. The mechanism of tolerance is still unknown. We have previously demonstrated that chronic diazepam administration in rats result in tolerance to the sedative and anxiolytic effects which is accompanied with a decrease in the interactions between GABA and benzodizepine binding sites (uncoupling) in cerebral cortex. The aim of this work was to investigate the molecular mechanism of benzodiazepine tolerance in an in vitro model of primary neuronal cultures from rat cerebral cortex. The exposure of cultured neurons to diazepam for 48 h produced a 40 % uncoupling (p<0.05) which was prevented in the presence of nifedipine, an inhibitor of L-type voltage-gated calcium channels (L-VGCCs). Benzodiazepine treatment also induced a 45 % decrease (p<0.05) in GABA-A receptor alpha1 subunit mRNA levels (p<0.05) that was inhibited by nifedipine. We hypothesized that the adaptive changes of GABA-A receptors induced by sustained exposure to benzodiazepine are mediated by a signaling pathway that involves activation of L-VGCCs. Results from calcium mobilization and nuclear run-on assays suggested that benzodiazepine exposure produces an increase in the calcium influx through L-VGCCs that activates an intracellular signaling cascade finally leading to the transcriptional repression of alpha1 subunit gene expression. Insights into the mechanism of benzodiazepine tolerance will contribute to the design of new drugs that can maintain their efficacies after long term treatments.